2005
DOI: 10.2134/jeq2005.0687
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Speciation in Broiler Litter and Turkey Manure Produced from Modified Diets

Abstract: Modifying poultry diets by reducing mineral P supplementation and/or adding phytase may change the chemical composition of P in manures and affect the mobility of P in manure-amended soils. We studied the speciation of P in manures produced by broiler chickens and turkeys from either normal diets, or diets with reduced amounts of non-phytate phosphorus (NPP) and/or phytase, using a combination of chemical fractionation and synchrotron X-ray absorption near edge structure (XANES) spectroscopy. All broiler litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 31 publications
8
102
3
2
Order By: Relevance
“…Particulate P was strongly tied to total P concentration in leachate (r 2 > 0.94), accounting for at least 58% to 64% of total P. The largest concentrations of particulate P were associated with the first rainfall simulation followed by the first irrigation event (figure 4a). Findings clearly implicated particulate P as a primary fraction of leached P, consistent with studies elsewhere that have evaluated leaching of P from manured soils (Toor et al 2005;Schelde et al 2006;Kleinman et al 2009). In those studies, however, liquid manures were evaluated.…”
Section: Resultssupporting
confidence: 86%
“…Particulate P was strongly tied to total P concentration in leachate (r 2 > 0.94), accounting for at least 58% to 64% of total P. The largest concentrations of particulate P were associated with the first rainfall simulation followed by the first irrigation event (figure 4a). Findings clearly implicated particulate P as a primary fraction of leached P, consistent with studies elsewhere that have evaluated leaching of P from manured soils (Toor et al 2005;Schelde et al 2006;Kleinman et al 2009). In those studies, however, liquid manures were evaluated.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, manures that have a greater proportion of phytate P will have decreased WSP concentrations and WSP:TP. Examination of the available literature reveals a similar trend in swine feces (Baxter et al, 2003;Leytem and Thacker, 2008), broiler litter (Maguire et al, 2004;Toor et al, 2005), and manure from laying hens (Leytem et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…Sulfur L-edge NEXAFS spectroscopy could provide complementary information to identify these sulfur moieties (Kasrai et al, 1996), but this technique only works well for samples that have large amounts of sulfur such as in coal (M. Kasrai, personal communication), and our attempt to resolve the organic sulfur species in humic substance extracts using S L-edge NEXAFS spectroscopy did not provide satisfactory results (D. Solomon, unpublished data 2005). While NEXAFS studies of organic phosphorus are rare (Toor et al, 2005;Sato et al, 2005), Beauchemin et al (2003) and Lombi et al (2006) demonstrated that P K-edge spectroscopy has great potential to investigate inorganic phosphorus species in long-term-fertilized, P-rich soils differing in pH, clay, and organic matter. In an experiment conducted in conjunction with wet chemical techniques to characterize the dominant solid-phase species of phosphorus, Beauchemin et al (2003) also showed that the results obtained by NEXAFS spectroscopy for calcium (r = 0.87)-related and aluminum or iron (r = 0.99)-related phosphorus species correlated very well with the HCl extractable and NaOH extractable inorganic phosphorus species obtained from sequential phosphorus fractionation technique, respectively.…”
Section: Relationship With Other Methodsmentioning
confidence: 99%